Efektifitas Lembar Balik dan Video Animasi Terhadap Pengetahuan Primigravida tentang Persiapan Persalinan - Meki Sri Yuni; Ruwayda Ruwayda; Herinawati Herinawati (Jurnal Kesehatan Komunitas, 2021)
Mortality and morbidity in pregnant and maternity women are major problems in developing countries. Three late is the unpreparedness of the mother or family in facing childbirth and is one of the causes of maternal death in Indonesia. Lack of knowledge of mothers about the preparation needed before delivery such as signs of labor and obstetric complications caused three late. The purpose of this research is to find out the effectiveness of counseling using flip charts and animated videos on primigravida knowledge about childbirth preparation at the Simpang Sungai Duren Health Center. Study it uses a quasi-experimental method by designing a two-group pretest-posttest design. The population in this study is all primigravida pregnant women who were at the Simpang Sungai Duren Health Center from January to March were 62 people. The sampling technique used the total sampling method with a sample of 62 people who were randomly divided into 2 groups, the statistical analysis test used the T-test. Based on the results of the study, 96.8% of primigravida knowledge was not good before being given counseling using flipchart media while 83.9% knowledge was not good before being given counseling using animated video media, after being given counseling the knowledge of primigravida increased to good as much as 90.3% on the media flipchart and 100% on animated video media. The mean of flipchart media is 84.51 and the mean of animation video media is 90.75. It can be interpreted that animated video media is more effective in increasing primigravida knowledge about childbirth preparation compared to media flip sheets. It is hoped that the results of this study can be disseminated to all health promotion workers so that in every outreach activity they can use animated video media.